Laparoscopic transgastric circumferential stapler-assisted vs. endoscopic esophageal mucosectomy in a porcine model - Steinemann, Daniel C.; Zerz, Andreas; Müller, Philip C.; Sauer, Peter; Schaible, Anja; Lasitschka, Felix; Schwarz, Anne-Catherine; Müller-Stich, Beat P.; Linke, Georg R. (Endoscopy, 2017)
Background and study aims Extensive endoscopic mucosal resection (EMR) for Barrett’s esophagus (BE) may lead to stenosis. Laparoscopic, transgastric, stapler-assisted mucosectomy (SAM) with the retrieval of a circumferential specimen is proposed. Methods SAM was evaluated in two phases. The feasibility of SAM and the quality of specimens were assessed in eight animals. The mucosal healing was evaluated in a 6-week survival experiment comparing SAM (n = 6) with EMR (n = 6). The ratio of the esophageal lumen width (REL) at the resection level measured on fluoroscopy at 6 weeks divided by the width immediately after resection was compared. Results In all animals, a circular mucosectomy specimen was successfully obtained, with a median area of 492 mm2 (interquartile range [IQR] 426 – 573 mm2) and 941 mm2 (IQR 813 – 1209 mm2) using a 21 mm and 25 mm stapler, respectively. In the survival experiments, symptomatic stenosis developed in two animals after EMR and in none after SAM. The REL was 0.27 (0.18 – 0.39) and 0.96 (0.9 – 1.04; P < 0.0001) for EMR and SAM, respectively. Conclusions SAM provides a novel technique for en bloc mucosectomy in BE. In contrast to EMR, mucosal healing after SAM was not associated with stenosis up to 6 weeks after intervention.